CITIZEN SCIENCE PROJECT'S CONTRIBUTION TO SCIENCE LEARNING OUTCOME: SYSTEMATIC LITERATURE REVIEW - Ipin Aripin; Topik Hidayat; Nuryani Y. Rustaman; Riandi Riandi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
The research on the contributions of Citizen Science (CS) at the school and university levels has primarily focused on the technical execution of projects undertaken by participants. Rarely has it measured the types of contributions these projects have on the science learning outcomes of the participants. This study aims to understand various types of Citizen Science Projects and their contributions to science learning achievements at the school and university levels. The study employs the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, consisting of five stages: identification, scanning, eligibility, dan inclusion. The research findings identify 19 types of CSPs that contribute to science learning achievements at the school and university levels. Six indicators of science learning outcomes are measured through the implementation of CSPs in science education, both in schools and universities. These indicators include interest in science and the environment, motivation for learning science, self-efficacy, knowledge of content and scientific processes, science inquiry skills, and environmental awareness. The contributions of CSPs to these measured indicators of science learning outcomes show positive and significant results. Based on the research findings, it can be concluded that CSPs contribute to science learning outcomes through input, output, and nurturant effects resulting from the implementation of CSPs. Educators can incorporate CSPs into science education to facilitate more optimal science learning.